Marsupial Gut Microbiome - Chong, Rowena; Cheng, Yuanyuan; Hogg, Carolyn J.; Belov, Katherine (Frontiers in Microbiology, 2020)
The study of the gut microbiome in threatened wildlife species has enormous potential to improve conservation efforts and gain insights into host-microbe coevolution, especially on microbial fermentations in herbivorous species. Threatened species are often housed in captivity, and during this process undergo considerable changes to their gut microbiome. Studying the gut microbiome of captive animals therefore allows identification of dysbiosis and opportunities for improving management practices in captivity and for subsequent translocations. Manipulation of the gut microbiome through methods such as faecal transplant may offer an innovative means of restoring dysbiotic microbiomes in threatened species to provide health benefits. Finally, characterization of the gut microbiome (including the viral components, or virome) provides important baseline health information and may lead to discovery of significant microbial pathogens. Here we summarise our current understanding of microbiomes in Australian marsupial species.